Atomistic simulation of [100](001) crack propagation with Cu precipitates in α-iron. (1st December 2021) - Yin, Jian; Hou, Huaiyu; Wang, Jing Tao; Liu, Xiangbing; Xue, Fei
Abstract: Fracture properties of Reactor Pressure Vessel (RPV) steel have significant effects on its service life and the nuclear safety. In this work, Molecular Dynamic (MD) simulation has been performed to investigate [100](001) crack propagation in α-iron. The influences of temperature and the Cu precipitates on the crack propagation were studied. In the simulation, twinning bands induced by the slipping of partial dislocation were observe. While we increased the simulation temperature or introduced the Cu precipitates to the model, the dislocation cross-slip behavior was observed, which reduced the peak stress and made the crack easier to initially propagate. However, it is revealed from the simulation results that the Cu precipitates resisted the further crack propagation, especially for the Cu precipitates with diameter larger than 3 nm. In addition, the Cu precipitates on the pre-crack plane represent better resistance to crack propagation than other locations. Furthermore, comparing the RPV steel with the copper-containing steel, it is concluded that the smaller size of Cu precipitates and the higher service temperature of RPV steel are the main reason of the embrittlement induced by Cu precipitates. Highlights: The influences of temperature and Cu precipitates on the crack propagation were studied using Molecular Dynamic simulation. Both the high temperature and introduced Cu precipitates would reduce the peak stress of the crack propagation. The smaller sizes of Cu precipitates and the higher service temperature are the main reason of RPV steel embrittlement.